Environmental Conservation Values in Zawawi Imron's Literature: An Ecosemantic Study - Ismatul Izzah; Darni Darni; Mintowati Mintowati (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to uncover environmental conservation messages contained in Zawawi Imron's literary works through an ecosemantic approach. Ecosemantics, as a branch of ecological linguistics, focuses on the relationship between the meaning of language, nature, and culture. Zawawi Imron, a poet known as the "Sea Poet," has produced many ecologically nuanced works, representing the harmonious relationship between humans and nature, particularly in the context of Madurese coastal culture. This study uses a descriptive qualitative method with content analysis techniques on selected poems by Zawawi Imron. The results of the study indicate that these works are full of conservation messages such as calls to protect the sea, care for the land, maintain local wisdom, and warnings against environmental damage caused by human activity. Through the poet's distinctive diction, metaphors, and imagery, these messages are not only aesthetic, but also ethical and ecological. This study concludes that literature can be an important medium in building ecological awareness and strengthening environmental conservation values rooted in local culture.